2022
DOI: 10.2147/ijgm.s392767
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Use of Proton Pump Inhibitors Increases Cardiovascular Events in Patients with Coronary Heart Disease

Abstract: Antiplatelet drugs, as the cornerstone of the treatment of coronary heart disease, control the progression of the disease, but bring a higher risk of gastrointestinal bleeding. Relevant guidelines recommend the use of proton pump inhibitors (PPIs) to minimize the risk of gastrointestinal bleeding in patients receiving dual antiplatelet therapy. But for people at low risk of gastrointestinal bleeding, the harms associated with routine use of PPIs may far outweigh the benefits. PPIs increase the risk of lower ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Two studies have argued that inappropriate use of PPIs has unnecessarily increased the risk of adverse cardiovascular outcomes. Hu et al in 2022 and Ma et al in 2022 both reported an increased ASCVD risk associated with GERD, especially in patients without indications for the medications [35,47,48,57].…”
Section: Medical Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies have argued that inappropriate use of PPIs has unnecessarily increased the risk of adverse cardiovascular outcomes. Hu et al in 2022 and Ma et al in 2022 both reported an increased ASCVD risk associated with GERD, especially in patients without indications for the medications [35,47,48,57].…”
Section: Medical Therapymentioning
confidence: 99%
“…PPIs and H2RAs are frequently prescribed to patients with both GERD and concomitant coronary artery disease or previous myocardial infarctions due to concerns about chronic excess gastric acid secretion with chronic NSAID, antiplatelet, and/or anticoagulant agents and the increased risk for upper gastrointestinal bleeding [48]. However, new data suggests that PPIs may play a role in the incidence, progression, and mortality of cardiovascular disease [49].…”
Section: Medical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…As PPI use increases worldwide, growing concerns about PPI complications have been raised [ 6 , 7 , 8 ]. Specifically, drug interaction with clopidogrel, which is an antiplatelet agent classified as thienopyridines, has been postulated in many recent studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Both PPIs and clopidogrel are metabolized by hepatic cytochrome P450 (CYP) enzymes; in the presence of CYP2C19 inhibition, PPIs could reduce the efficacy of clopidogrel’s protective roles in cardiovascular events [ 22 ].…”
Section: Introductionmentioning
confidence: 99%